(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A series of tests were performed to examine the effect of induced nano-composites on behaviors of the expansive clay. Tests were carried out at different polymer contents and curing time. The induced nano-composites within the swelling clay can be attributed to non-plastic properties and acted as a hydraulic binder with lesser swelling potential.